大功率减速器弧齿锥齿轮模态分析 - 封艳秋; 赵继云; 陈世其 (Jixie chuandong)
The three-dimensional model of spiral bevel gear of large power reducer is established based on Pro/E.The linear statics analysis and modal analysis are carried out by using ANSYS Workbench,and the natural frequency and vibration mode are obtained.The simulation results serve as a reference in dynamic design of gear transmission system.